Exploring Students' Speaking Anxiety - Rani Yulia Nuridzdzati; Suvi Akhiriyah (Universitas Muhammadiyah Barru, 2023)
Speaking anxiety is significant to make students develop anxious feeling during speaking in the target foreign language, even high achiever students. Therefore, this research aimed to (i) discover the extent of speaking anxiety factors emerging in high achiever students and (ii) perceive high achievers’ speaking anxiety to their speaking performance. This qualitative research applied a descriptive phenomenological approach to analyze and elaborate on the data. The research subjects were 8 high achiever students of SMK Negeri 5 Surabaya. All of them were interviewed using focus group discussion to explore their speaking anxiety and its impact on them. The results revealed (i) three factors of speaking anxiety namely, communication apprehension, fear of negative evaluation, and test anxiety were experienced by high achiever students along with elements of each factor; (ii) several contributions were constructed according to high achievers’ perceptions. The example of a positive contribution was the consideration to take speaking fluency as a challenge they required to conquer. While negative contribution was such feeling nervous and uncomfortable to speak in front of their peers, led them to the speaking anxiety symptoms appearance (rapid heartbeat, blank, and stuttered) during conveying their ideas, being reluctant to speak due to weakened bond of students-instructor related, and struggling to recalibrate the memory during performing speaking tests.